Kesenjangan Kesiapan Petani terhadap Teknologi Biogas Tongkol Jagung: Tinjauan Pengetahuan, Sikap, Keterampilan, dan Harapan - Sri Adelila Sari; Nur Basuki; Amrizal Amrizal; Ali Fikri Hasibuan; Hanisah Hasibuan; Feri Yuni Asiyah Kabeakan; Rani Febriana; Elena Hasian Sitompul; Ribka Eliada Sitorus; Deby Febriyanti (Pusat Riset dan Inovasi Nasional, 2025)
Corn cob waste poses a potential environmental problem and is an underutilized resource. Converting corn cobs into biogas offers a dual solution: managing waste while providing a renewable energy source for farmers. This study was aimed to assess the knowledge, attitudes, skills, and expectations of corn farmers regarding the processing of corn cob waste into biogas. The research was conducted in Desa Maholida, Sttu Jehe, Pakpak Bharat, using a descriptive survey method. A total of 40 corn farmers taken from several farmer groups in the village were selected as respondents. The instrument used was a closed questionnaire with a Likert scale comprising 5 items each to measure these four aspects (knowledge, attitudes, skills, expectations). Study findings indicated that farmers' knowledge, attitudes, and skills respectively showed low percentages, namely 27%, 35%, and 22%. These low levels constituted a significant barrier to the effective adoption and sustainability of the biogas program. On the other hand, all respondents (100%) expressed high optimism that the biogas program could improve their quality of life. This study reveals challenges in adopting corncob biogas technology, the gap between farmers' aspirations and implementation capacity. It recommends targeted socialization and training to enhance biogas adoption, environmental sustainability, farmers' welfare.